2021
DOI: 10.1097/md.0000000000027756
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of global research output in congenital cataracts from 1903 to 2021

Abstract: Background and aim: Globally, congenital cataract remains one of the main causes of visual loss in children. This study was designed to plot the overall research output and evaluate some key bibliometric indicators in congenital cataracts research. Methods: Publications on congenital cataracts were retrieved from the Web of Science Core Collection database. The published literature was searched using the keywords “congenital cataract” OR “congenital cataracts” in the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…This may be due to the availability of funding in the field of research [11] . The finding of our study is in line with other studies [13][14][15][16][17][18]. More research is needed to be done in this field, and researchers, especially from disease polio-endemic countries should be encouraged to carry on the research and share their findings in peer-reviewed journals.…”
Section: Discussionsupporting
confidence: 90%
“…This may be due to the availability of funding in the field of research [11] . The finding of our study is in line with other studies [13][14][15][16][17][18]. More research is needed to be done in this field, and researchers, especially from disease polio-endemic countries should be encouraged to carry on the research and share their findings in peer-reviewed journals.…”
Section: Discussionsupporting
confidence: 90%
“…The United States is the leading country in psychooncology research productivity and is home to most of the top institutions and funding agencies in this field. Previously published bibliometric studies in different research fields also reported the highest contribution from the United States, such as congenital cataracts (Idriss et al, 2021), exosomes (Shi et al, 2021), fascioliasis (Ahmad et al, 2021c), hepatitis (Ahmad et al, 2021e,f), myocardial infarction (Zhou et al, 2018), pediatric trauma (Ahmad et al, 2021b), psychosomatic (Shah et al, 2021), tuberculosis (Nafade et al, 2018), and vaccines (Zhang et al, 2019;Ahmad et al, 2021a,d).…”
Section: Discussionmentioning
confidence: 94%
“…In the WoSCC, the search was limited to publication year (1904–2021), document type (article), publishing language (English), and WoSCC index (Science Citation Index Expanded (SCI-Expanded)). The WoSCC database was preferred because it is widely used in bibliometric studies and provides essential information on journals and other bibliometric indices [ 32 , 33 , 34 , 35 , 36 , 37 ]. The online search was performed on 13 October 2021 and updated on 27 May 2022, by the lead author (TA).…”
Section: Methodsmentioning
confidence: 99%